Recent Trends in Bank Privatization - Bertay, Ata Can; Calice, Pietro; Diaz Kalan, Federico Alfonso; Masetti, Oliver (World Bank, Washington, DC, 2020)
This paper revisits trends in bank privatization and analyzes their economic impact over the past 25 years. Building on a novel data set of privatization events for 70 developed and developing countries, it shows that bank privatization became more frequent since the Global Financial Crisis, especially in emerging markets such as China and India, but also smaller in that the fraction of a bank's ownership relinquished during privatization events declined. The majority of privatizations happened via public sales in domestic capital markets. The banks that were chosen to be privatized tended to underperform their peers and had weaker asset quality pre-privatization, but the empirical evidence on banks' post-privatization performance is mixed. The paper finds that privatized banks turn toward more traditional banking models and increase credit extension with no apparent negative distributional implications. However, the analysis does not reveal significant differences in bank profitability post-privatization, although differences exist between developed and developing countries. Notably, banks that have been recapitalized prior to privatization perform significantly better afterward privatization.